Survival prognostic factors in patients undergoing cytoreductive surgery and hyperthermic intraperitoneal chemotherapy treatment: analysis from a single oncological center. Issue 1 (December 2016) - Graziosi, L.; Marino, E.; De Angelis, V.; Rebonato, A.; Donini, A.
Abstract Background The aim of our study is to analyze survival, treatment-related morbidity, and safety in our experience of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Methods Sixty-four patients were treated. Survival curves were calculated according to the Kaplan-Meier method. Univariate and multivariate analyses were done, and Cox's proportional hazard model was used to identify significant factors. Results Global 5-year overall survival was 55 %. Overall survival was also evaluated according to neutrophils to lymphocytes ratio and neutrophils to platelets ratio. Overall survival according to pre-operative serum albumin level shows a difference in the two groups (P < 0.05). We observed minor or no adverse events in 53 cases (89.8 %), while 3 patients (5.1 %) showed a grade III–IV complication and 3 post-operative deaths (5.1 %). Post-operative complication also influenced overall survival; patients in whom a minor complication occurred had a 3-year overall survival (OS) of 62 % vs. a 3-year OS of 28 % in patients who underwent a major complication (P < 0.1). Conclusions Hyperthermic intraperitoneal chemotherapy (HIPEC) could be a valid and feasible option for selected patients affected by gastrointestinal malignancies' peritoneal carcinomatosis. Pre-operative parameters could be evaluated to choose patient who could benefit from cytoreductive surgery and hyperthermic intraperitoneal chemotherapy.